The wasp genus Sphex in Sub-Saharan Africa (Hymenoptera: Sphecidae) - Thorleif H. Dörfel; Michael Ohl (European Journal of Taxonomy, 2022)
The Afrotropical species of the sphecid genus Sphex are revised. Forty-six taxa are recognized, of which fifteen are newly described: Sphex abbotti nivarius subsp. nov., S. comorensis sp. nov., S. hades sp. nov., S. nefrens sp. nov., S. occidentalis sp. nov., S. pseudopraedator sp. nov., S. pseudosatanas sp. nov., S. pulawskii sp. nov., S. rufoclypeatus sp. nov., S. satanas memnon subsp. nov., S. schmideggeri sp. nov., S. schoutedeni malawicus subsp. nov., S. socotrensis sp. nov., S. stadelmanni rufus subsp. nov. and S. victoria sp. nov. A new subgenus, Menkeella subgen. nov., is proposed for S. paulinierii Guérin Méneville, 1843.